Firm Specific Factors dan Profitabilitas Sub-Sektor Properti di Indonesia - Muhammad Madyan; Putri Yanti Lestyarini; Novian Abdi Firdausi (Universitas Airlangga, 2019)
This study analyzes effects of firm specific factors to the profitability of property and real estate sub-sector which listed in BEI in time period of 2010-2015. Firm specific factors are measured with liquidity, financial leverage, firm size, and firm growth as generally used determinants. This reasearch used purposive sampling method at 33 firms which fulfill the research criterions, which are firms listed consistently in BEI’s property and real estate sub-sector, also publishing financial statements routinely during research period. Analysis proceeded by using multiple linear regression with study results show that liquidity and financial leverage have negative effects to profitability, while firm size and firm growth have positive effects to profitability.